2012
DOI: 10.1007/s00468-012-0695-6
|View full text |Cite
|
Sign up to set email alerts
|

Differences in cold tolerance and expression of two fatty acid desaturase genes in the leaves between fingered citron and its dwarf mutant

Abstract: Fingered citron (Citrus medica L. var. sarcodactylis Swingle), a precious fruit ornamental plant, is sensitive to low temperature. Cold tolerance, evaluated by semi-lethal temperature, was lower in wild-type 'Qingpi' than in its mutant 'Aihua' trees obtained by c-radiation. The full-length cDNAs of two genes encoding fatty acid desaturases involved in unsaturated fatty acid biosynthesis were isolated from the fingered citron leaves. The Cms-FAD2 open reading frame (ORF) had 1,152 bp and was uninterrupted, enco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 14 publications
(32 reference statements)
0
8
0
3
Order By: Relevance
“… 52 demonstrated that cold acclimation of olive drupes relied on FAD post-transcriptional regulation. Conversely other studies demonstrated that transcription of ω-6 desaturase was up-regulated by cold in cotton 53 , citrus 54 and cucumber 55 . In contrast, cold induced a rapid and transient expression of the plastidial desaturase fad6 in embryos of the tolerant hybrid only (Fig.…”
Section: Discussionmentioning
confidence: 76%
“… 52 demonstrated that cold acclimation of olive drupes relied on FAD post-transcriptional regulation. Conversely other studies demonstrated that transcription of ω-6 desaturase was up-regulated by cold in cotton 53 , citrus 54 and cucumber 55 . In contrast, cold induced a rapid and transient expression of the plastidial desaturase fad6 in embryos of the tolerant hybrid only (Fig.…”
Section: Discussionmentioning
confidence: 76%
“…sarcodactylis. Swingle showed that the expression level of the two genes correlated with the genotypes of the two plants [ 25 , 26 ]. In Arabidopsis , two types of omega-3 FADs ( FAD3 located in the ER and FAD7 / 8 located in the chloroplast) catalyze the formation of TA [ 7 , 26 , 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, fingered citron is very cold-sensitive and cannot tolerate frost, so it can only be grown outdoors in south Florida or in protected locations in central and north Florida. At temperatures below 45°F, fingered citron leaves wilt, photosynthetic rates decrease, and in severe cases, the tree dies (Guo et al 2009;Yang et al 2012). In areas with frost, trees can be transplanted to big containers and overwintered indoors with sufficient sunlight.…”
Section: Cultivation Practicesmentioning
confidence: 99%
“…In areas with frost, trees can be transplanted to big containers and overwintered indoors with sufficient sunlight. Plant flowering and fruiting can also stagnate if undergoing cold stress (Yang et al 2012). Fruit matures and is ready to harvest from November to January, but eventually some fruits may appear year-round.…”
Section: Cultivation Practicesmentioning
confidence: 99%
See 1 more Smart Citation